Metaphor or not Metaphor: Is that the question? - Drößiger, Hans-Harry (Respectus Philologicus, 2020)
This review concerns the volume Metaphor Identification in Multiple Languages. MIPVU around the world, edited by Susan Nacey, Aletta G. Dorst, Tina Krennmayr and W. Gudrun Reijnierse, published by John Benjamins Publishing Company, Amsterdam & Philadelphia, 2019.